Cancer in Japan: Prevalence, prevention and the role of heterocyclic amines in human carcinogenesis. (December 2016) - Nagao, Minako; Tsugane, Shoichiro
Abstract In this article, three topics are being studied in order to understand the present state of cancer in Japan. First, the statistics on cancer mortality indicates that the mortality from cancer in young individuals has been decreasing during the last 50 years, although the total mortality from cancer has been steadily and steeply increasing. Second, epidemiological analyses of cancer causes in Japan indicated that 50 % of cancer cases are preventable, and that prevention of infection and refraining from tobacco smoking will reduce cancer mortality by about 40 %. Third, mutagenic/carcinogenic heterocyclic amines present in cooked meat/fish have been suggested to be carcinogenic in humans in many epidemiological studies carried out in Japan and other countries.